Optimalisasi Peningkatan Usaha Ekonomi Produktif Bagi Orang Tua dengan Anak Disabilitas di Desa Ngawonggo Kecamatan Tajinan Kabupaten Malang - Juli Astutik; Budi Suprapto; Abidin, Zaenal (Jurnal Pengabdian Tri Bhakti, 2024)
This Internal Community Service (PMI) program aims to improve the family economy, parents with children with disabilities through training and mentoring “making pastries of various shapes and flavors”. The activity was carried out, considering that since the Covid 19 pandemic all community activities have completely stopped for more than 3 years, as well as the activities of the association of parents with children with disabilities. This community service program is an alternative to opening a home industry business for parents with children with disabilities. The participants of this program are parents with children with disabilities who are members of the “Bintang Harapan” association in Ngawonggo Village, Tajinan District, Malang Regency. Methods used: lectures and mentoring. As a result of the implementation of this service, partners can: 1) gain knowledge of making pastries with various flavors and variants, 2) able to practice themselves directly based on direction and guidance from experts (related to the manufacturing process from selecting ingredients to the production of pastries), 3) partners have their own equipment as a result of grants from the service team. The suggestions/recommendations are: 1) the ability of partners in making pastries can be used as an alternative opportunity to open a pastry business, 2) in the future it is necessary to design a trademark as branding of productive economic businesses 3) in the medium term it is necessary to think about a marketing strategy so that the business can run smoothly and sustainably.